AKUNTABILITAS DAN TRANSPARANSI DALAM MENINGKATKAN KUALITAS SISTEM MANAJEMEN KEUANGAN MASJID DI KOTA MEDAN - Julkarnain Julkarnain (JRAM (Jurnal Riset Akuntansi Multiparadigma), 2018)
The mosque is a non-profit organization and donated from various sources such as zakat, infak, and wakf donations. In regard to financial statement, this organization might use standard accountance system as widely lnown as Financial Report Standard or called Pernyataan Standar Akuntansi Keuangan (PSAK) No. 109. The system is stressing on transparency and accountability. It is interesting therefore, to study more regarding both accountability and transparency of financial system which is applied in the mosque organizations located in the Medan City. This case study involved 5 mosques in the area of Medan City were; Masjid Raya Al-Mashun mosque, Ikhlasiyah Mosque, Jami 'Al-Munawarrah Mosque (at Islamic University of North Sumatera), Silaturrahim Mosque and Ismail Mosque. This study consisted of three variables; accountability and transparency as independent variables and financial management of the mosque as dependent variable. The questionnaire was employed for data collection and distrusted to 34 respondents around the five mosques as the research subjects.The results shows that the influence of accountability and transparency of financial report to the mosque financial management in Medan City was simulatneousely significant. The statistical analysis involved f test with coefficient of determination and the result show 83,7% while the rest of 16,3% are other factors not examined by the author.